Defining Developmental Regression in Rare Neurodevelopmental Disorders of Genetic Etiology: A Scoping Review - Kummeling, Joost; Maria van de Wiel, Evy Antoinette; Veeken, Lara Dora; Maria Egger, Jos Ignatius; Kleefstra, Tjitske; Vermeulen-Kalk, Karlijn (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Some genetic neurodevelopmental disorders (NDDs) are linked to a loss of acquired abilities. No universal term or severity measure exists for this phenomenon. This scoping review aims further to define developmental regression in NDDs of genetic etiology. Method: We used the PRISMA checklist and searched PubMed, medRxiv, and Google Scholar for developmental regression literature. After data extraction, qualitative (e.g., assessment methods) and quantitative (e.g., mentioned NDDs) data were analyzed. Results: A total of 59 relevant articles from 2074 unique records were identified, associating 18 NDDs of genetic etiology with developmental regression. Multiple terms (e.g., loss of skills, deterioration) and definitions were used across syndromes. Conclusions: A uniform definition of developmental regression was formulated based on literature diversity and NDD heterogeneity. The study also offers guidance on identifying and monitoring developmental regression and its underlying causes.